Effect of Sims modified posture on the rotation and descent of the fetus in women during their first delivery with epidural analgesia - Ana Mª Ruíz Rey; Rosa Mª Rodríguez Ferrer; Gema Magdaleno del Rey; Mª Belén Feijoo Iglesias; Rosa Ana Martín de Vega (NURE Investigación, 2011)
Objective: To assess whether Sims modified posture reduces the duration of the second labor stage of delivery and cases rotation and the descent of the fetus by the delivery channel in nulliparous women with epidural analgesia. Method: Randomized clinical trial with a group control (Sims and semi-Fowler) and a group of intervention (modified Sims). Scope and subjects of study: nulliparous women with epidural analgesia in delivery room Hosp. Univ. La Paz (Madrid) during 2008-2009. Results: 157 cases: control group (52.9%) [43 Sims (27.4%), 40 semi-Fowler (25.5%)]; experimental group 74 modified Sims (47.1%). No relevant differences were found between: type of delivery and adopted posture (p = 797), or in the time between the various postures [experimental group 66.76 minutes (IC95%=62.09-71.46), control group of 67.54 minutes (IC95%=62.64-72.44) (p = 0. 939)], or association between the posture, rotation and descent of fetus, the 91.6% delivers in front posture. The most common alterations DIP Variables (39.5%), followed by the combination of DIP Variables and DIP I (13.4%).Conclusions: The data show no significant differences between the rotation, the descent and time needing fetal presentation to reach the level VI of Hodge. There were also no differences between postures and delivery type. Supine postures were more comfortable to women.